X-ray spectro-polarimetry analysis of the weakly magnetized neutron star X-ray binary GX 9+1 - Tarana, A.; Capitanio, F.; Gnarini, A.; Fabiani, S.; Ursini, F.; Bianchi, S.; Ferrigno, C.; Parra, M.; Cocchi, M.; Farinelli, R.; Matt, G.; Soffitta, P.; et al. (EDP Sciences, 2025)
We present an X-ray spectro-polarimetric study of the weakly magnetized neutron star low-mass X-ray binary GX 9+1, utilizing data from the Imaging X-ray Polarimetry Explorer (IXPE), alongside simultaneous NuSTAR, NICER, and INTEGRAL observations. GX 9+1, located in the Galactic bulge, is a persistently bright atoll source known for its spectral variability along the color–color diagram. Our spectral analysis during the soft state confirms that the emission is dominated by a soft blackbody and thermal Comptonization components, with no evidence of a hard X-ray tail. Moreover, these observations suggest a relatively low-inclination system (23° < i < 46°) with a weak reflection component, consistent with emission from the accretion disk and neutron star boundary layer. Spectro-polarimetric analysis reveals no significant polarization in the 2–8 keV range, with a 3σ level upper limit on the polarization degree of 1.9%. However, marginal evidence of polarization is detected in the 2–3 keV band at the 95.5% confidence level (2σ), suggesting potential contributions from scattering effects in the individual spectral components (disk, reflection, and Comptonization) that may cancel each other out due to the different orientations of their polarization angles. This behavior aligns with other atoll sources observed by IXPE, which typically exhibit lower and less variable polarization degrees compared to Z–class sources.